Technomoral Resilience as a Goal of Moral Education. - Bauer, Katharina; Hermann, Julia (Ethical Theory & Moral Practice, 2024)
In today's highly dynamic societies, moral norms and values are subject to change. Moral change is partly driven by technological developments. For instance, the introduction of robots in elderly care practices requires caregivers to share moral responsibility with a robot (see van Wynsberghe 2013). Since we do not know what elements of morality will change and how they will change (see van der Burg 2003), moral education should aim at fostering what has been called "moral resilience" (Swierstra 2013). We seek to fill two gaps in the existing literature: (i) research on moral education has not paid enough attention to the development of moral resilience; (ii) the very limited literature on moral resilience does not conceptualise moral resilience in relation to new technological developments. We argue that philosophical accounts of moral education need to do justice to the importance of moral resilience, and that a specific form of moral resilience should be conceptualised as "technomoral resilience" to underline the added value of cultivating moral resilience in relation to technomoral change. We illustrate the role of technomoral resilience in practice by looking at the context of elderly care. To make the first step towards an account of how technomoral resilience can be fostered in moral education, we propose that moral education shall focus on a triangle of capacities: (1) moral imagination, (2) a capacity for critical reflection, and (3) a capacity for maintaining one's moral agency in the face of disturbances.